Gender, Nilai Intrinsik Pekerjaan, Penghargaan Finansial dan Pertimbangan Pasar Kerja terhadap Minat Mahasiswa Berkarir sebagai Akuntan Publik - Arifatin Nur Afifah; Dyah Ratnawati (IPM2KPE, 2022)
This study aims to determine the effect of gender, work intrinsic value, financial rewards, and labor market considerations on student interest in a career as a Public Accountant. The research method used is a quantitative method. The analysis technique uses multiple linear regression analysis with the help of SPSS 25. The sampling technique uses probability sampling. The sample used in the study was 70 students. The results showed, a) Gender variable (X1) obtained a value of tcount (0.746) < ttable (1.998) with the direction of the regression coefficient and p value (0.458) > level of significance (α = 0.05); b) The intrinsic value of work variable (X2) obtains a value of tcount (2.426) > ttable (1.998) with a positive regression coefficient direction and p value (0.018) < level of significance (α = 0.05); c) The financial award variable (X3) obtained a value of tcount (2.474) > ttable (1.998) with a positive regression coefficient direction and p value (0.016) < level of significance (α = 0.05); d) The labor market consideration variable (X4) obtained a value of tcount (3.372) > ttable (1.998) with a positive regression coefficient direction and p value (0.001) < level of significance (α = 0.05). In conclusion, the intrinsic value of work, financial rewards, and labor market considerations partially have a significant effect on student interest in a career as a public accountant, while gender has no significant effect on student interest in a career as a public accountant. Keywords: Gender, Public Accountant Career Interests, Work Intrinsic Values, Financial Rewards, Labor Market Considerations